The Protection of Human Dignity, Honour and Reputation in ECtHR Case-law Concerning the Right to Respect for Private Life (Article 8 ECHR) - Mateeva, Ekaterina (Yearbook of the Law Department, 2022)
Human dignity is considered to be “the mother of all human rights”. It is absolute and cannot thus be restricted. The protection of human dignity is the core principle embodied in the set of rules on human rights. The provision of article 8, § 1 of the Convention for the Protection of Human Rights and Fundamental Freedoms (ECHR) lays down that everyone has the right to respect for his private and family life, his home and his correspondence. On various occasions, ECtHR considered that despite the lack of an explicit mention of a human’s reputation and one’s dignity and honour within the text of Article 8 of ECHR, they are still being encompassed by the protective function of this provision. A reasoning is found in the notion that the aforementioned protective function embodies “the right for private life” thus including the human right to a dignified existence. Still, ECtHR did point out that Article 8 ECHR is a possible means to provide legal protection to honour, reputation and dignity solely “where primarily the internal aspect of honour is at stake”, more specifically, when one’s self-assessment and self-value are harmed. On the contrary, whenever the external aspect of honour has been harmed, i. e., reputation and public assessment of an individual, this should be considered as a freedom of expression case under Article 10, para. 2 ECHR (corresponding to Article 39, paragraph 2 of the Bulgarian Constitution).